Natural Regeneration Enhances Long‐Term Soil Carbon Storage in Various Fractions More Effectively Than Active Restoration: Meta‐Analysis - Yuqian Ye; Ruiyang Zhang; Dashuan Tian; Jinsong Wang; Guirui Yu; Shuli Niu (Global Change Biology, 2025)
Restoration of terrestrial ecosystems, through both natural and active approaches, is critical for enhancing soil organic carbon (SOC) storage. However, the long‐term effects of these restoration approaches on soil aggregate organic carbon remain poorly understood. In this study, we conducted a global meta‐analysis to assess the temporal effects of natural and active restoration on SOC and aggregate organic carbon, including macroaggregate (MAC), microaggregate (MIC), and silt‐clay fraction (SCC) organic carbon. The overall global results showed that natural regeneration outperformed active restoration in enhancing SOC and MAC, with increases of 21% and 24%, respectively, higher than those of active restoration. Notably, the benefits of natural regeneration on SOC and MAC intensified over time, surpassing active restoration after 40 years. In different terrestrial ecosystems, natural regeneration showed greater effectiveness in late‐stage SOC and MAC accumulation, with 72% and 61% higher in forests (> 40 years) and 64% and 63% higher in grasslands (> 20 years) compared to active restoration. In shrublands, late‐stage (> 15 years) MIC accumulation was 62% higher under natural regeneration than under active restoration. In addition, natural regeneration enhanced SOC storage in deeper soil layers and in carbon‐poor areas. These findings highlight the long‐term superiority of natural regeneration for soil carbon sequestration, positioning it as a key strategy for sustainable ecosystem restoration and climate change mitigation.